The heritage designed by farming. The past meets the future at Spout House Farm in Lake District. - Gallo, Anna (OS. Opificio della Storia, 2022)
The Lake District has been the UK’s largest national park since 1951 and has been a World Heritage Site since 2017. The Lake District owes its cultural and economic importance mostly to the interaction between agro-pastoral farming and its natural features. A balance recently put at risk by modernity due to critical issues related to the aging of farming communities, animals’ diseases, the milk price de-crease and the intensification of tourism as risk for the environment. A balance recently put at risk by modernity due to critical issues related to the aging of farming communities, animals’ diseases, the milk price decrease and the intensification of tourism as risk for the environment. The paper aims to explore and analyse the role of farming in the area, with a focus on the village of Crosthwaite and the old manorial farm called Spout House that represents a physical and immaterial heritage, as is one of the few remaining working farm in the valley. Built in the 17th Century, despite the architecture still unaltered, the predominant activity of farming has become a much smaller part in the last years, making room for another type of economy based on tourism. A practice that needs to be integrated in the heritage in order to give new life to the rural dimension.